Analisis Integritas dan Skeptisisme Profesional terhadap Kepatuhan Auditor pada Standar Profesional Akuntan Publik - Najla Kayla; Mia Lasmi Wardiyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Auditors' compliance with the Public Accountant Professional Standards (SPAP) is the main concern in maintaining the quality and trust of the audit process, especially in the face of increasingly complicated audit tasks. This study aims to evaluate the level of integ-rity and skepticism of auditors in supporting compliance with SPAP. This study uses a de-scriptive qualitative approach with observation methods and document studies. The object of the research is the Public Accounting Firm Dra. Yati Ruhiyati, data was obtained from direct observation during the field professional practice period and analysis of relevant audit documents. The results of the study show that the integrity of auditors can be seen from consistency in carrying out audit stages, compliance with established procedures, and clarity in audit documents. The professional skepticism of auditors can be seen from the cautious attitude in evaluating audit evidence, including the application of additional checks before drawing conclusions. These findings show that compliance with SPAP is not only formal, but also highly dependent on the auditor's professional attitude. This study shows the importance of increasing the integrity and professional skepticism of auditors as part of efforts to improve quality and compliance in audit practices in Public Accounting Firms.